Closer look at circulating nitric oxide levels and their association with polycystic ovary syndrome: A meta-analytical exploration - Seyed Sobhan Bahreiny; Akram Ahangarpour; Elnaz Harooni; Mahdi Amraei; Mojtaba Aghaei; Reza Mohammadpour Fard (International Journal of Reproductive BioMedicine)
Background: Polycystic ovary syndrome (PCOS) casts a wide shadow over the reproductive health of millions of women worldwide, emerging as one of the most complex and multifaceted endocrine disorders. In addition, nitric oxide (NO) stands out as a pivotal signaling molecule, orchestrating a symphony of physiological processes. Objective: This meta-analysis aims to elucidate the association between NO levels and PCOS, investigate the potential of NO as a biomarker for PCOS diagnosis, and evaluate its clinical significance. Materials and Methods: A systematic review was conducted in several electronic databases, including PubMed, Web of Science, Cochrane Library, Scopus, EMBASE, and Google Scholar, to identify relevant studies published up to January 2024. Standardized mean difference and 95% CI were calculated using a random effects model to assess the overall effect size. Meta-regressions and subgroup analysis were performed to investigate sources of heterogeneity. Results: A meta-analysis of 14 studies with 1171 participants showed that NO levels were significantly lower in the PCOS group than in the control group. The pooled analysis yielded a standardized mean difference of -0.482; 95% CI: -0.908 to -0.056; p = 0.027. Subgroup analyses further demonstrated variations in NO levels between different PCOS phenotypes and in relation to metabolic parameters. Conclusion: This meta-analysis provides evidence for an association between PCOS and dysregulated NO levels and suggests a potential role of NO as a biomarker in the diagnosis and pathogenesis of PCOS.